The Time of the Last Hunters: Chronocultural Aspects of Early Holocene Societies in the Western Mediterranean - Perrin Thomas (Open Archaeology, 2023)
In the Western Mediterranean Basin, the last hunter-gatherer societies fall within a chronological range between the 9th and 5th millennia cal. BCE, that is, between the cold oscillation of the Younger Dryas and the Holocene climatic optimum, before disappearing under the expansion of the first Neolithic societies. The variability in cultural expressions is very high, as shown by the variability in the lithic industries, a technical field which, from a historiographical point of view, is the preferred approach of archaeologists to address these issues. However, convergences in technical choices or typological features show the existence of major currents of diffusion and exchange between many of these Mesolithic groups. But the discussion of these cultural dynamics requires knowing precisely the absolute chronology of these groups and the detailed characteristics of their material productions. The aim of this article is so to re-examine the chronocultural organization of the Mesolithic of the Western Mediterranean, especially the first part of it, roughly from the middle of the 10th millennium cal. BCE to the middle of the 6th, on the basis of a critical revision of the absolute dates.